Arbuscular Mycorrhizal Fungi Negatively Affect Nitrogen Acquisition and Grain Yield of Maize in a N Deficient Soil - Wang, Xin-Xin; Wang, Xiaojing; Sun, Yu; Cheng, Yang; Liu, Shitong; Chen, Xinping; Feng, Gu; Kuyper, Thomas W. (Frontiers in Microbiology, 2018)
Arbuscular mycorrhizal fungi (AMF) play a crucial role in enhancing the acquisition of immobile nutrients, particularly phosphorus. However, because nitrogen (N) is more mobile in the soil solution and easier to access by plants roots, the role of AMF in enhancing N acquisition is regarded as less important for host plants. Because AMF have a substantial N demand, competition for N between AMF and plants particularly under low N condition is possible. Thus, it is necessary to know whether or not AMF affect N uptake of plants and thereby affect plant growth under field conditions. We conducted a two-year field trial and pot experiments in a greenhouse by using benomyl to suppress colonization of maize roots by indigenous AMF at both low and high N application rates. Benomyl reduced mycorrhizal colonization of maize plants in all experiments. Benomyl-treated maize had a higher shoot N concentration and content and produced more grain under field conditions. Greenhouse pot experiments showed that benomyl also enhanced maize growth and N concentration and N content when the soil was not sterilized, but had no effect on maize biomass and N content when the soil was sterilized but a microbial wash added, providing evidence that increased plant performance is at least partly caused by direct effects of benomyl on AMF. We conclude that AMF can reduce N acquisition and thereby reduce grain yield of maize in N-limiting soils.